Предмет: Алгебра, автор: brkvcsyncd2088

ПОЖАЛУЙСТА! ПРИВЕДИТЕ ДРОБЬ! В;Г;Д;Е;Ж;З. ПОЖАЛУЙСТА!​

Приложения:

Ответы

Автор ответа: NNNLLL54
1

\dfrac{2y}{x-1}=\dfrac{2y(x^2+x+1)}{(x-1)(x^2+x+1)}=\dfrac{2y(x^2+x+1)}{x^3-1}\\\\\\\dfrac{3a}{a^2+ab+b^2}=\dfrac{3a(a-b)}{(a-b)(a^2+ab+b^2)}=\dfrac{3a(a-b)}{a^3-b^3}\\\\\\\dfrac{7}{y-b}=\dfrac{-7}{b-y}\\\\\\\dfrac{a}{a-10}=\dfrac{-a}{10-a}\\\\\\\dfrac{p}{p-2}=\dfrac{-p(p+2)}{(2-p)(2+p)}=\dfrac{-p(p+2)}{4-p^2}

\dfrac{a+3}{6-2a}=\dfrac{a+3}{-2(a-3)}=\dfrac{(a+3)^2}{-2(a-3)(a+3)}=\dfrac{-(a+3)^2}{2(a^2-9)}

Похожие вопросы